LEADERSHIP STYLE AND EFFECT ON SMALL MEDIUM ENTERPRISES: A SYSTEMATIC LITERATURE REVIEW - Chandraningtyas, Iva (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 8 No 1 (2022): The 8th International Conference Of Islamic Economics And Business (ICONIES 2022), 2022)
Research on SME Objects has been increasing recently. Leadership style is the key in enhancing performance organization. This article aims to do studies literature about style leadership both Transformational leadership and transactional leadership as well as their impact on SMEs. The study uses a systematic literature review. Keywords that used are Transformational leadership and SME, transactional leadership and SME. The limited articles in 2019-2020 were obtained from the journal database ScienceDirect. The results of 13 articles to be conducted analysis literature review. The study held in Indonesia, Ghana, Ecuador, India, South Asia, Pakistan, Tunisia, China, Vietnam, and Iraqi Kurdistan. Based on the results analysis article, transformational leadership provides a positive relationship to performance employees, quality life employees, OCB employees, knowledge sharing, satisfaction employees, and improved performance organization in SMEs. Whereas transactional leadership provides little impact _ even no give impact on the performance of SME organizations. results analysis also reveals that a study about transformational leadership and its impact on many SMEs conducted compared to with study about transactional leadership.